(untitled) (Web of Teachers: Inderscience Research, 2024)
This article is about the widespread promotion of a healthy lifestyle among students and the importance of a healthy lifestyle in the lives of young people. According to him, several main aspects of the formation of a healthy lifestyle are presented.